2011
DOI: 10.5230/jgc.2011.11.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Pattern of Lymph Node Metastasis Depending on the Location of Gastric Cancer

Abstract: PurposeWhen performing a laparoscopic assisted gastrectomy, a function-preserving gastrectomy is performed depending on the location of the primary gastric cancer. This study examined the incidence of lymph node metastasis by the lymph node station number by tumor location to determine the optimal extent of the lymph node dissection.Materials and MethodsThe subjects consisted of 1,510 patients diagnosed with gastric cancer who underwent a gastrectomy between 1996 and 2005. The patients were divided into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 22 publications
5
25
0
Order By: Relevance
“…Data showed sufficient safety for LN station #2 for the early cancers located in midbody and high body. A previously published study also showed low metastatic rate of these LN stations in middle or upper third EGC [32]. As a confirmation of this concept, the TG cases of this study with upper third involved tumor location, but tumor border of > 3 cm apart to EGJ had metastasis to each LN station similar to abovementioned database cases (no LN metastasis in LN station #2).…”
Section: Discussionsupporting
confidence: 88%
“…Data showed sufficient safety for LN station #2 for the early cancers located in midbody and high body. A previously published study also showed low metastatic rate of these LN stations in middle or upper third EGC [32]. As a confirmation of this concept, the TG cases of this study with upper third involved tumor location, but tumor border of > 3 cm apart to EGJ had metastasis to each LN station similar to abovementioned database cases (no LN metastasis in LN station #2).…”
Section: Discussionsupporting
confidence: 88%
“…The M lymphatic drainage has the characteristics of both U and L. The perigastric lymphatic drainages eventually flow into the lymph nodes surrounding the abdominal aorta. That study also reported that the characteristics of lymph node metastasis in gastric cancer generally follow the way of lymphatic drainage, which is consistent with previously reported findings (20). Several studies demonstrated that, for advanced gastric cancer, D2 dissection may significantly improve the patients' survival rate, whereas the number of removed lymph nodes is also significantly correlated with prognosis (21,22).…”
Section: Distribution Of Lymph Node Metastasissupporting
confidence: 89%
“…4 lymph nodes was >20%. Han et al (20) reported that the incidence of metastasis in station no. 4 lymph nodes in patients with proximal gastric cancer was ~12.6%.…”
Section: Distribution Of Lymph Node Metastasismentioning
confidence: 99%
“…Stations were considered mandatory for dissection (1) if the frequency of LN metastasis was ≥ 1% in EGC cases or (2) patients with positive LNs and AGC had a 5-year survival rate of ≥ 20%. In some papers investigating the frequency of LN metastasis in EGC, the incidence of perigastric lymph nodes was reported to be 1.2%-7%, suggesting that more than 1% of LN metastasis woule be suitable for mandatory dissection [16][17][18][19]. Also in our hospital data, 5-year survival after curative resection of gastric cancer showed that stage IIIa was 53.9%, IIIb was 36.5%, and IV was 23.9%.…”
Section: Methodsmentioning
confidence: 61%